PERKEMBANGAN PENELITIAN BIBLIOMETRIK PSAK 109 MENGGUNAKAN VOSVIEWER - Hastuti Olivia; Nurluthfiyyah Syarifah Hanun Siregar; Waha Rira Nadirah; Azzahra Inayatussyfa; Syahri Ramadhan Saragih (Bisnis-Net, 2023)
ABSTRACTStatement of Financial Accounting Standards (PSAK) 109 is an important guide considering the many problems regarding zakat, infaq and alms today. This interest has motivated many studies to review PSAK 109. The problem with this research is the suitability of amil zakat financial reporting, related to the disclosure of income from non-halal funds, as well as how to recognize and measure accounting for zakat, infaq/alms. This study aims to map the general description of PSAK 109 which has been discussed from previous articles by utilizing biliometric analysis. This research data is metadata extracted from the Google Scholar database from 2018 to 2023. All information is exported into Research Information Systems (RIS) format for analysis purposes using VOSviewer software. The number of document metadata collected is 252 articles. The results of the analysis show that between PSAK 109, zakat accounting, financial statements, OPZ, BAZNAS, zakat, infaq and alms are interconnected.Keywords: PSAK 109; zakat infaq and alms; BAZ; LAZ; VOSViewer.